(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to the World Health Organisation (WHO), the specific weight of laboratory investigations in modern medicine is more than 70% of the total number of different types of investigations performed on a patient [11,12].